Pulmonary herpes simplex infection: a case report - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; Abdullah, Suhaila; Syed Yasin, Sharifah Nor Ashikin (Consortium of Islamic Medical Colleges, 2021)
Pulmonary herpes simplex infection is rarely reported. To date, there is a paucity of literature on this infection. This case study describes a 64-year-old male with a background history of diabetes mellitus and hypertension who was intubated for acute respiratory failure. The managing team had difficulty to wean his oxygenation thus decided for bronchoscopy examination which showed suspicious growth at middle lobe of the right lung. Repeated bronchoscopy by pulmonologist revealed a nodular ‘warty’ appearance lesion at right bronchus intermedius. His biopsy revealed histopathological changes consistent with herpes simplex infection.